Performance study of low-speed wind energy harvesting by micro wind turbine system - Kadhim, M. A.; Phing, C. C.; Wai, L. C.; Paw, Johnny Koh Siaw; Yaw, Chong Tak; K., Kadirgama; Kadhim, A. A. (Elsevier Ltd, 2025)
Wind energy constitutes a fundamental clean and sustainable energy asset, serving an essential function in the worldwide shift towards a low-carbon energy framework. Notwithstanding the technological innovations that have improved the accessibility and operational efficiency of wind power, the intrinsic variability of wind velocity and flow patterns continues to present considerable obstacles to the advancement of wind turbines that can rival conventional energy sources in terms of operational performance and reliability. To address these obstacles, the current research endeavor is dedicated to the augmentation of energy extraction from low-velocity wind environments through the implementation of micro-scale wind turbine systems. By utilizing maximum power point tracking (MPPT) algorithms, this study investigates the operational strategies of wind turbines subjected to variable wind conditions, with a particular focus on optimizing energy capture during low to moderate wind speeds. In addition, the research delineates targeted design recommendations aimed at improving the efficacy of small-scale wind turbines in low-velocity circumstances. A hybrid economic-environmental strategy is underscored as a viable approach to mitigate the unpredictability associated with wind energy, thereby integrating renewable energy systems with energy storage mechanisms. This research endeavor aims to facilitate the advancement of efficient, environmentally sustainable, and economically viable wind energy technologies that are meticulously tailored for small-scale implementations